La justicia comunitaria y la lucha por una ley de coordinación de la justicia - Brandt, Hans-Jürgen (2017)
The Constitution of Peru claims a law, which regulates the coordination of the indigenous justice with the national judicial system. But since 1993 when the Constitution was enacted, Congress has failed to fulfill this task. The article describes the problems resulting from this legal vacuum and substantiates the need for a law of intercultural coordination of the judiciaries. However, the content of the required law is controversial. In the discussion four currents of opinion can be determined. The end points are characterized, on the one hand, by the «minimalists», who want to reduce the legal competences of the communities to a minimum, and the «maximalists», on the other hand, who advocate unlimited competences of the indigenous judiciary. The article analyzes the arguments of the different currents of opinion and identifies the challenges of the legislative work.